The dreamtime - Chernov, Mstyslav (Academic Studies Press, 2022)
"A fusion of documentary and psychological thriller inspired by true events conceived and written over an eight-year period. Drawing on the Indigenous Australian concept of dreamtime, the novel explores a society's collective experience of war and conflict and is based on real events that the author, a war correspondent and photojournalist, witnessed during the war in eastern Ukraine and the migration crises in southern Europe over recent years"--